Construção e automatização de um reator CSTR para práticas de controle de sistemas online - Santos, Gabriel Teixeira (2019)
The present paper was developed with the objective of constructing a CSTR reactor with a cooling jacket using an Arduino® microprocessor for level and temperature control and a DOIT brand ESP32 microprocessor for online communication. Additionally, a styrofoam box was built with Peltier boards and heat sinks to act as a refrigeration system. The experiments showed consistent results for a proportional control of level and temperature. Although the coherent results, the refrigeration system have not achieved the necessary potency to ensure its efficiency in long tests.